Pengaruh Pengalaman Kerja Terhadap Prestasi Kerja Pegawai - Andika Putra Irawan (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
To test and analyze the relationship between the influence of motivation on work performance for employees of the Maritime, Fisheries and Food Security Service of Manggarai Regency. The research results show that: 1). Simultaneously, work experience and motivation have a significant effect on improving the work performance of employees of the Manggarai Regency Maritime Fisheries and Food Security Service, showing a calculated F value of 2.005 with a significance level known from the sig value of 0.002 (smaller than 0.05). . 2). Partially, work experience and motivation have a significant effect on increasing work performance of employees of the Manggarai Regency Maritime Affairs, Fisheries and Food Security Service. Based on the results of the t test, it is known that work experience has a dominant effect on work performance. employees of the Manggarai Regency Maritime Affairs, Fisheries and Food Security Service; proven by the calculated t value of 1.400 with a significance level of 0.003 (smaller than 0.05).